Fabrication and testing of a power operated axial flow seed extractor - DEEPTHI SUSAN P. E JACINTHA T JOSEPH GEORGE K MANSOOR ALI K.C; Er. Santhi Mary Mathew (Guide) (Tavanur 1993 Kelappaji College of Agricultural Engineering and Technology)
mechanical seed extraction reduces the cost of seed production, improves the quality of seed and prevent the hazards cased to the manual labour during seed extraction.
Fabrication and testing of a power operated axial flow seed extractor